2016
DOI: 10.1093/ajcp/aqw134
|View full text |Cite
|
Sign up to set email alerts
|

Stromal PD-L1 Expression Is Associated With Better Disease-Free Survival in Triple-Negative Breast Cancer

Abstract: PD-L1 expression is seen in a high proportion of TNBCs and associated with better DFS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 29 publications
4
46
1
Order By: Relevance
“…In particular, PD‐L1 expression has been positively and independently associated with DFS/RFS and/or OS in several unselected primary BC cohorts . In addition, when considering specific BC subtypes, it has been suggested that PD‐L1 protein expression may retain a positive prognostic role in TNBC and in HER2+ BC, in both trastuzumab‐treated and untreated patients .…”
Section: Methodsmentioning
confidence: 99%
“…In particular, PD‐L1 expression has been positively and independently associated with DFS/RFS and/or OS in several unselected primary BC cohorts . In addition, when considering specific BC subtypes, it has been suggested that PD‐L1 protein expression may retain a positive prognostic role in TNBC and in HER2+ BC, in both trastuzumab‐treated and untreated patients .…”
Section: Methodsmentioning
confidence: 99%
“…Stromal cells express the immune-checkpoint protein programmed cell death 1 ligand 1 (PD-L1). The effect of stromal PDL1 expression on immunotherapy outcomes is currently unclear, with some studies showing an association with a better prognosis for patients with breast cancer 269 , but also a poor prognosis for patients with adult T-cell leukaemia 270 .…”
Section: Effects Of Tumour Stroma On Therapymentioning
confidence: 99%
“…Although the PD-L1 expression on TILs has not yet been thoroughly examined in the literature, it seems from the existing studies that it is of great prognostic value (61). From these studies PDL1IC expression has shown to have opposite prognostic value compared to PDL1TC expression, since most cases are related to higher DFS, RFS as well as OS (41,62). Zhao et al (61) studied the prognostic value of PDL1IC expression on several solid tumors, and indicated that it is a positive prognostic factor, especially in IBC.…”
Section: Figure 1 (A) Pd-l1 Expression In Tumor Cells (×20) (B) Pd-mentioning
confidence: 99%